ANALISIS KOMPENSASI PEGAWAI NEGERI PADA POLRI DALAM KEPEMILIKAN RUMAH LAYAK HUNI DI POLRI - Eko Wahyono; Ridwan Rajab; Mala Sondang Silitonga (Jurnal Academia Praja, 2024)
Home is very important for life because it is one of the basic needs for humans besides clothing and food. Every individual human being will prioritise the fulfilment of basic needs over secondary needs, as well as the need for a house, everyone will try Qualitative descriptive method was used in this study. Data collection techniques commonly used in qualitative research are observation, interviews, and documentation. In addition, Sofyandi (2008) argues that to increase the productive contribution of an organisation's human resources, human resource management is defined as a strategy for applying management functions, namely planning, organising, leading, and controlling, in all human resource activities and operations, starting from attraction, selection, training and development, placement, and so on. Fair and competitive work compensation can motivate PNPPs to achieve higher work performance. Work compensation is one of the important factors that influence work motivation. Job satisfaction can be influenced by the extent to which employees are satisfied with the compensation they receive. High job performance tends to contribute to job satisfaction.